2015
DOI: 10.1061/(asce)gt.1943-5606.0001215
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach for Health Monitoring of Earthen Embankments

Abstract: The proposed methodology was used and validated on a recently built 2 km long river 29 embankment in Galston (Scotland, UK). A suite of geotechnical probes was installed to 30 monitor the seasonal variation of water content over a two-year period. Most devices were 31 calibrated in-situ. A novel procedure to extrapolate the value of water content from the 32 geotechnical and geophysical probes in any point of the embankment is illustrated. 33Desiccation fissuring degrades the resistance of embankments against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…TDR has recently been used to monitor earth structures such as levees in controlled experiments and in real field case studies (Scheuermann et al 2009;Utili et al 2015;Janik et al 2017). Estimating the degree of saturation (S r ) would be very beneficial as this parameter is directly linked to the stability of earth structures and could be used to trigger warnings (Valentino et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TDR has recently been used to monitor earth structures such as levees in controlled experiments and in real field case studies (Scheuermann et al 2009;Utili et al 2015;Janik et al 2017). Estimating the degree of saturation (S r ) would be very beneficial as this parameter is directly linked to the stability of earth structures and could be used to trigger warnings (Valentino et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Estimating the degree of saturation (S r ) would be very beneficial as this parameter is directly linked to the stability of earth structures and could be used to trigger warnings (Valentino et al 2011). Measuring the soil parameters remotely from buried sensors would clearly be advantageous and reduce the current reliance on the visual qualitative inspections conducted by inspection engineers (Utili et al 2015). Studies using electrical resistivity tomography (ERT) have shown the potential of using and S r for monitoring the condition of ageing embankments and have suggested that these parameters can be used for a more effective management of geotechnical assets Gunn et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the locations of the cracks (problem iii ) are prescribed in the search for the most unfavourable failure mechanism. These maps can be employed for two purposes: ( i ) in the case of earth structures prone to fissuring, as for instance flood defence embankments , they may help inspection engineers to reduce significantly the extension of the zones to be inspected by excluding the zones where cracks have no detrimental effect on slope stability; ( ii ) when the presence of one or more cracks in a slope is known, the maps tell the geotechnical engineer whether the crack may be discarded from the stability analysis of the slope.…”
Section: Introductionmentioning
confidence: 99%
“…These are only indicative, and may vary considerably for the wide range of possible sites and geology that could fall into each category. Utili et al (2015) described the use of monitoring information to consider the stability of longer lengths of asset. An overview for consideration of slopes at the corridor scale has been given by Dijkstra et al (2014) (continued) (Chambers et al 2011) and Nafferton embankment, Northumberland, UK (Glendinning et al 2014) are being used to assess the performance of new monitoring instruments and techniques.…”
Section: What To Monitormentioning
confidence: 99%